PENGARUH KEAMANAN, PRIVASI, DAN REPUTASI TERHADAP KEPERCAYAAN KONSUMEN ONLINE SHOPPING DI KOTA PADANG - Nurhatinah Nurhatinah (Jurnal Ecogen, 2018)
This research aims to understand the Influence of security, privacy, and reputation toward trust in online shopping consumer. The purpose of this research are: (1) the effect of security toward trust in online shopping consumer, (2) The effect of privacy toward trust in online shopping consumer, (3) The effect of reputation toward trust in online shopping consumer, (4) The effect of security, privacy, and reputation toward trust in online shopping consumer. The type of research used in this study was a causal quantitative research. The population in this study was citizens of Padang city, that has been to online shopping. The sampling technique employed in this study was purposive sampling method with the total samples of 100 people. The data collection technique used in this study was questionnaire that has been tested for validly and reliability. The data analysis technique employed in this study to answer the hypothesis was multiple regressions. The result of this study shows that partially independent variable security (X1) significantly influenced the trust in online shopping consumer, privacy variable (X2) significantly influenced the trust in online shopping consumer, and reputation variable (X3) significantly influenced the trust in online shopping consumer. Simultaneously, variables security, privacy, and reputation significantly influenced trust in online shopping consumer.Keyword: Trust In Online Shopping Consumer, Security, Privacy, and Reputation.